SAT0029 THE IMMUNE-PATHOGENIC CHARACTERISTICS OF AUTOREACTIVE B CELLS AGAINST CITRULLINATED ANTIGENS IN RHEUMATOID ARTHRITIS. (June 2019) - Kristyanto, Hendy; Voort, Ellen van der; Kerkman, Priscilla; Burgers, Leonie; Brinck, Robin Ten; der Helm - van Mil, Annette van; Baeten, Dominique; Huizinga, Thomas; Toes, Rene; Scherer, Hans Ulrich
Abstract : Background: Autoreactive B cells are critical mediators of autoimmune pathology. At present, little is known about the functional and phenotypic characteristics of these cells in human autoimmune disease. Rheumatoid arthritis (RA), a common autoimmune disease, is characterized by the presence of disease-specific anti-citrullinated protein antibodies (ACPA). Different lines of evidence indicate that CD20+ B cells, and in particular the citrullinated antigen-specific, ACPA-expressing subset, are critically involved in disease pathogenesis. Objectives: To delineate the molecular make-up of ACPA-expressing B cells and to define their pathogenic effector functions. Methods: Protective tetanus toxoid (TT)-specific and autoreactive ACPA-expressing B cells were identified and analyzed directly ex-vivo from individual RA patients and from ACPA-positive individuals at-risk for developing disease. Both antigen-specific cell populations were enumerated and phenotypically characterized by flow cytometry. In addition, ACPA-expressing B cells were isolated and functionally analyzed in B cell culture systems. Results: In contrast to TT-specific B cells from the same patients, ACPA-expressing B cells were larger in size and strongly expressed CD19, HLA-DR, CD80, CD86 and the proliferation marker Ki-67, while down-regulating CD32. This activated phenotype was less pronounced in ACPA-positive 'at-risk' arthralgia patients. Furthermore, ACPA-expressing B cells in blood of RA patients secreted elevated levels of pro-inflammatory cytokines, in particular IL-8, upon stimulation and did so spontaneously as differentiated plasmablasts/-cells in synovial fluid. Notably, ACPA-expressing B cell-derived IL-8 induced neutrophil migration in vitro. Conclusion: Our findings provide first evidence that ACPA-expressing B cells are well equipped to activate T cells, actively differentiate into IL-8 producing plasmablasts and, hence, could attract neutrophils to the rheumatoid joint. These findings define important phenotypic and functional characteristics of autoreactive B cells in a prototypic human autoimmune disease. They point to a direct pathogenic role of ACPA-expressing B cells in the inflammatory disease process underlying RA and favour approaches that aim at their antigen-specific depletion. Disclosure of Interests: Hendy Kristyanto: None declared, Ellen van der Voort: None declared, Priscilla Kerkman: None declared, Leonie Burgers: None declared, Robin ten Brinck: None declared, Annette van der Helm - van Mil Grant/research support from: The research leading to these results has received funding from the European Research Council (ERC) under the European Union's Horizon 2020 research and innovation programme (Starting grant, agreement No 714312) and from the Dutch Arthritis Foundation.The funding source had no role in the design and conduct of the study., Dominique Baeten Employee of: UCB Pharma, Thomas Huizinga Consultant for: Merck, UCB, Bristol Myers Squibb, Biotest AG, Pfizer, GSK, Novartis, Roche, Sanofi-Aventis, Abbott, Crescendo Bioscience Inc., Nycomed, Boeringher, Takeda, Zydus, Epirus, Eli Lilly, Rene Toes Grant/research support from: Sanofi, Hans Ulrich Scherer Grant/research support from: Sanofi, BMS